Correlation between outcome and severity of organophosphorus poisoning according to peradeniya organophosphorus poisoning scale - Sah, Sunny Kumar; Das, Sunil Kumar (Journal of General Practice and Emergency Medicine of Nepal, 2024)
Introduction: Organophosphates are widely used pesticides. These are linked to significant global poisoning cases, with around 563,000 deaths annually, particularly in rural agricultural areas, due to agents like parathion and chlorpyrifos. This study focuses on the Peradeniya Organophosphorus Poisoning (POP) scale, which assesses severity based on clinical parameters and may be particularly useful in resource-limited settings. Method: This study aims to correlate the severity of organophosphate poisoning, measured by the POP scale, with clinical outcomes such as atropine dosage, hospital stay, need for ventilator support, and mortality. Conducted over one year (March 2021 – Feb 2022) at Emergency Department of Patan Academy of Health Sciences in Nepal, it is a prospective, cross-sectional study including patients who presented within 24 hours of organophosphate ingestion, without prior treatment. Data were collected using POP scale to assess symptom severity and track clinical outcomes, with a calculated sample size of 43. Result: Among total 43 patients, 25(58.1%) were male, with majority (45(81.4%)) classified as having mild poisoning according to the POP scale. The average atropine dose and ICU stay were similar between genders, though hospital stay was significantly longer for males. There was a significant correlation between POP scores and clinical outcomes including the amount of atropine required, ICU stay, and total hospital stay. No severe cases or deaths were recorded. Conclusion: The POP scale effectively correlates with the severity and outcomes of organophosphate poisoning. Its application can aid in early diagnosis, prioritization of treatment, and resource allocation in emergency settings, potentially improving patient management and outcomes in regions with limited medical infrastructure.